Rasio Likuiditas, Rasio Solvabilitas, Rasio Rentabilitas Koperasi Jasa Keuangan Syariah Di Jawa Tengah - Rahmat Nuryanto; Muhammad Tho'in; Herlina Kusuma Wardani (Jurnal Akuntansi dan Pajak, 2014)
This study aims to determine the ratio of liquidity, solvency and profitability which is the financial performance of KJKS Mass Group Sragen. The research method has been done in the form of quantitative descriptive percentage. The research data is obtained from financial report of KJKS Mass Group Sragen. The results showed that: (1) Based on the liquidity ratio shows the amount of good or liquid in the analysis of Current Ratio is 122.01% in 2012 and 153.11% in 2013, while the Cash Ratio analysis shows good results because it is still far below predefined standards; (2) Given the solvency ratio shows good or unbreakable results in meeting its obligations and short term; (3) Meanwhile, based on profitability or profitability ratios indicate that KJKS Mass Group is not rentable in generating maximum net profit.